Application of modular design strategy in the life cycle of household appliances under the goal of carbon neutrality - Sun, Jialin (International Scientific Technical and Economic Research, 2025)
Modular design, a key strategy for achieving carbon neutrality in home appliances, provides a systematic solution for the industry's green transformation by restructuring carbon footprint management across all stages of the product lifecycle. This study systematically analyzes the application mechanisms of modular design in the design, production, use, and recycling stages of home appliances, revealing its carbon reduction benefits through three pathways: extending product lifespan, improving resource utilization efficiency, and promoting a circular economy. The study shows that home appliances employing modular design can reduce carbon emissions over their entire lifecycle by over 30%, with reductions of 15% in production, 10% in use, and 5% in recycling. The study further explores challenges facing modular design, including technical standards, market acceptance, and policy support, and proposes strategies such as establishing an open modular platform, innovating service models, and strengthening the standard system. Finally, the study explores the potential of modular design, enabled by digital technology, intelligent carbon management, business model innovation, and the construction of cross-industry circular systems, providing theoretical basis and practical guidance for the home appliance industry's path to carbon neutrality.